An Epidemiological and Therapeutic Study of the Cryptosporidium parvum Parasite in Some Farm Animals in Anbar Province /Iraq - Suad Shallal Shahatha (Journal of Global Pharma Technology, 2016)
This study was conducted to investigate of Cryptosporidium parvum parasite in some farm animals in Anbar Province by examining 564 feces samples (148 sheep, 144 cows, 132 goats, and 140 chickens). The results showed that the infection rates of the examined animals were 35.8 %, 41.6 %, 34.8 % and 25.7 % respectively. There were no significant differences (p ≥ 0.05) between the sexes in infection. The infection rate in small age’s groups was 46.5% while the large age’s groups 21.4 %. Significant differences were observed (p ≥ 0.05) between infection rates in rural areas and urban areas (44.9 %, 21.1) % respectively. The study also involved an effect of a water extract of the Zygophyllum fapago plant (also locally known as Chicken choking plant (on Cryptosporidium parvum parasite growth. As part of this study, a concentration of between 0.05-5 mg/ml was used. The application of these concentrations led to an inhibitory effect on parasite growth - an application of relatively higher concentrations caused greater effects in times of growth between 1-5 days.Keywords: Epidemiological, Cryptosporidium parvum, Animals, Extract, Anbar.